Vulvovaginal atrophy in the peri- and post-menopause: relevance and impact on quality of life - Mekan R. Orazov; Elena S. Silantyeva; Viktor E. Radzinsky; Liudmila M. Mikhaleva; Elizaveta A. Khripach; Evgeny D. Dolgov (IP Berlin A.V., 2022)
Vulvovaginal atrophy (VVA) is detected in more than 50% of postmenopausal women, and at 4049 years of age, 15-19% of women have relevant signs. Atrophic changes in the female urogenital system are associated with hypoestrogenism, which results in the defective synthesis of collagen and elastin due to reduced functional activity of fibroblasts. Although the symptoms of genitourinary syndrome of menopause significantly impair the quality of life, women rarely seek medical help for urogenital symptoms, considering them a normal condition for the period of aging. We searched Cochrane Library, PubMed, Science Direct, and ELibrary databases for the keywords vulvovaginal atrophy, genitourinary syndrome of menopause, quality of life, epidemiology, and postmenopausal age for 20122022. The literature review suggests that the prevalence of VVA is extremely high but underestimated due to the infrequent seeking of medical care by female patients with relevant symptoms. The genitourinary syndrome of menopause dramatically impacts patients' quality of life, but not all women eligible for treatment receive it. One of the reasons for refusing hormonal treatment is patients' fear of the systemic effects of hormonal drugs. There is an unmet need for alternative non-hormonal therapies. The objective is to analyze and systematize the scientific data accumulated over the past ten years on the epidemiology of VVA, its impact on patients' quality of life, and the challenges in diagnosing and treating the disease.